A novel route to copper(ii) detection using 'click' chemistry-induced aggregation of gold nanoparticles - Hua, C.; Zhang, W.; De Almeida, S.; Ciampi, Simone; Gloria, D.; Liu, G.; Harper, J.; Gooding, J. (Royal Society of Chemistry, 2012)
A simple colorimetric method for the detection of copper ions in water is described. This method is based on the 'click' copper(i)-catalyzed azide-alkyne cycloaddition reaction and its use in promoting the aggregation of azide-tagged gold nanoparticles by a dialkyne cross-linker is described. Nanoparticle cross-linking, evidenced as a colour change, is used for the detection of copper ions. The lowest detected concentration by the naked eye was 1.8 µM, with the response linear with log(concentration) between 1.8-200 µM. The selectivity relative to other potentially interfering ions was evaluated.